Impact of Online Science Learning on Children Aged 5-6 During the COVID-19 Pandemic: A Case Study at Barunawati Kindergarten 3 Samarinda: Dampak Pembelajaran Sains Secara Online pada Anak Usia 5-6 Tahun selama Pandemi COVID-19: Studi Kasus di TK Barunawati 3 Samarinda - Evie Palenewen; Tamara Dewi Audiya; Fachrul Rozie (Borneo Educational Journal (Borju), 2023)
The objective of this research is to provide a depiction of the effects of online science education on children between the ages of 5 and 6 amidst the COVID-19 pandemic, specifically in relation to the development of science learning abilities in this age group. This research aims to investigate the challenges and barriers encountered during the execution of science education for children aged 5–6 years at Barunawati 3 Samarinda Kindergarten. The research employs a case study methodology, which centers on the individuals involved in a particular teacher's online science learning case, as a means of adapting to crisis situations. The Barunawati 3 Samarinda Kindergarten has been accredited as "Good" based on the school's established criteria for evaluation. The study employed the interaction model proposed by Milles and Huberman to analyze the data collection methods, which included direct interviews, direct observation, and documentation, with a sample of one teacher, three parents, and three students. The findings indicate that the effects of incorporating online science education were facilitated via WhatsApp Video Calls and assignments completed by students with parental involvement. Additionally, the study examined student reactions during learning activities and the outcomes of instructional methods that did not employ digital learning resources. Hence, the findings of this research offer valuable insights for educational institutions to enhance their online science education programs, thereby facilitating a smooth transition of children to formal schooling.